Improving the Independence of Small and Medium Enterprises through Strengthening the Management of Plastic Waste Management Businesses in Kedung Kandang District, Malang City - Rita Indah Mustikowati; Maris Kurniawati; Chandra Sundaygara (Institut Teknologi dan Bisnis Asia Malang, 2023)
Purpose: Plastic recycling is important for environmental conservation and is also a form of business unit that provides employment opportunities for the surrounding community. The plastic waste management business has good prospects, because the reality is that until now the raw materials for plastic recycling production still have to be imported to meet production needs. This Community Partnership Empowerment (PKM) focuses on efforts to increase the independence of small and medium enterprises (SMEs) engaged in the management and recycling of plastic waste. Method: The methods used to overcome the problems faced by partners are business management training through business planning for business development, so that partner businesses tend to stagnate and training in applying financial management properly, so that the development of capital, assets, and business profits has not been measured. Conclusion: increase partner independence through strengthening plastic waste management business management and increase partner knowledge about a comprehensive management system